REFLECTION GOOD NAME AND CORRUPTION BEHAVIOR IN INDONESIA FROM PROVERBS 22:1 - Ester Agustini Tandana (QUAERENS: Journal of Theology and Christianity Studies, 2023)
This study investigates the relationship between maintaining a good name and the prevalence of corruption behavior in Indonesia. By conducting an exegetical analysis of Proverbs 22:1, which emphasizes the value of a good name, the research explores its relevance to the issue of corruption in the Indonesian context. The research explores the socio-cultural significance of a good name in Indonesian society and its impact on individual and collective behavior. It examines the perception of integrity and the role of reputation in shaping ethical conduct among public officials, business leaders, and citizens. The study also reviews existing literature, case studies, and empirical evidence related to corruption in Indonesia. Drawing insights from Proverbs 22:1, which states that "A good name is more desirable than great riches; to be esteemed is better than silver or gold," the research highlights the moral and spiritual dimensions of reputation and their potential influence on mitigating corruption. The findings provide valuable insights into the relationship between a good name, ethical behavior, and the prevalence of corruption in Indonesia. The study emphasizes the importance of fostering a culture of integrity, accountability, and transparency to effectively combat corruption. It also offers recommendations and strategies for individuals, institutions, and policymakers to promote and uphold a good name in the Indonesian context, to reduce corruption and its detrimental effects on society. This study contributes to the existing literature on corruption and ethics by examining the significance of a good name in addressing corruption behavior in Indonesia. It serves as a foundation for further research, policy development, and initiatives aimed at promoting integrity and combating corruption in the country.